SELECTION OF CHILDREN BY SPORTS - Ўразбаев Жахонгир Темур ўғли (American Journals Publishing, 2025)
The modern system of selection of children in various sports requires a comprehensive and scientifically based approach. This article discusses the main criteria of sports selection, including physiological, psychological and motor characteristics of children.
Keywords: Sports selection, children's sports, physiological indicators, psychological stability, sports specialization, individual characteristics.